2017
DOI: 10.1001/jamadermatol.2016.4129
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in Dermatology Clinical Trials

Abstract: he growth of the minority population in the United States is outpacing the growth of the non-Hispanic white population. Current projections estimate that the United States will achieve "majority-minority" status in which minority populations total over 50% of the overall population by 2044. 1 This demographic shift has not been reflected in medical research. African Americans, Hispanic individuals, and women are underrepresented in clinical 2 and randomized controlled trials generally, 3 as well as within spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 17 publications
6
101
6
Order By: Relevance
“…Despite the high prevalence of AD in skin of colour populations, there is little data on the efficacy of common therapies for AD in non‐White ethnic groups. This is, at least in part, due to underrepresentation of some races in clinical trials as well as lack of subset analyses by race . Of AD clinical trials published between 2000 and 2009, only 59.5% of studies included race and ethnicity as baseline demographic information .…”
Section: Treatment Of Atopic Dermatitismentioning
confidence: 99%
“…Despite the high prevalence of AD in skin of colour populations, there is little data on the efficacy of common therapies for AD in non‐White ethnic groups. This is, at least in part, due to underrepresentation of some races in clinical trials as well as lack of subset analyses by race . Of AD clinical trials published between 2000 and 2009, only 59.5% of studies included race and ethnicity as baseline demographic information .…”
Section: Treatment Of Atopic Dermatitismentioning
confidence: 99%
“…For clinicians, more attention on the differences would help make earlier diagnoses, personalize physician-patient conversations, and advocate for further education on this issue in residency training programs. Potentially greater impact on QOL with scalp psoriasis 2,5,a Greater BSA involvement in Asian patients 6 More severe disease at presentation 7,a Treatment Preference for foams and lotions for scalp 2,a UV consideration for prevention of hyperpigmentation 8 No known differences in efficacy of systemic treatments 5 Patients with skin of color underrepresented in clinical trials 9 Reduced patient recognition of certain treatments 10 Psychosocial impact Higher DLQI at baseline 6,a Abbreviations: QOL, quality of life; BSA, body surface area; DLQI, dermatology life quality index.…”
Section: Resultsmentioning
confidence: 99%
“…It is more likely to report favorable outcomes for industry-sponsored studies [ 31 ]. In our study, only 6.25% of the trials reported the funding source, whereas nearly 70% of dermatology RCTs from PubMed database described the funding source [ 32 ].…”
Section: Discussionmentioning
confidence: 99%